Using tools of classical dance technique for improving performance of turns young gymnasts - Батєєва Наталія Петрівна (Nataliya Batieieva); Кызим Пётр Николаевич (Petr Kyzim); Тіткова Ірина Олександрівна (Irina Titkova); Луценко Лариса Сергіївна Larisa Lutsenko (Slobozhanskyi Herald of Science and Sport, 2014)
Purpose: in theory to work out and experimentally ground the methods of teaching of classic dance, sent to perfection of technical trade of implementation of turns gymnasts on the stage of base pre-treatment. Material and methods: in research seven gymnasts took part in age 8-9 years. Results: the use of facilities of classic dance in the applied new methods considerably improved quality implementation of turns gymnasts: estimation of implementation of dough «turn «passе» on a right foot» increased on 40%; dough «turn of «the attitude» on a right foot» – on 32%; dough «turn «ring by means of hands» on a right foot» – on 33%. Conclusions: it is set that the increase of level of choreographic preparation of gymnasts by perfection of technique of implementation of base elements of classic dance is provided by reliability of execution of turns in a calisthenics on the stage of base pre-treatment. The offered methods on perfection of level of technical trade of implementation of turns rendered the effective affecting development of coordinating capabilities and technical preparedness of gymnasts.